Fishery yields vary with land cover on the Amazon River floodplain - Leandro Castello; Laura L Hess; Ram Thapa; David G McGrath; Caroline C Arantes; Vivian F Renó; Victoria J Isaac (Fish and Fisheries, 2018)
Inland fisheries underpin food security in many tropical countries. The most productive inland fisheries in tropical and subtropical developing countries occur in large river–floodplain systems that are often impacted by land cover changes. However, few studies to date have assessed the effects of changes in floodplain land cover on fishery yields. Here, we integrated fisheries and satellite‐mapped habitat data to evaluate the effects of floodplain deforestation on fishery yields in 68 floodplain lake systems of the lower Amazon River, representing a wide range in relative amounts of woody, herbaceous and non‐vegetated land cover. We modelled relative fish yields (fish capture per unit effort [ CPUE ]) in the floodplain lakes as a function of the relative amounts of forest, shrub, aquatic macrophyte and bare/herbaceous habitats surrounding them. We found that forest amount was positively related ( p = .0003) to multispecies CPUE . The validity of these findings was supported by rejection of plausible alternative causative mechanisms involving habitat‐related differences in amount of piscivores, fishing effort, lake area, and habitat effects on CPUE of the nine taxa dominating multispecies yields. Our results provide support to the idea that removal of floodplain forests reduces fishery yields per unit effort. Increased protection of floodplain forests is necessary to maintain the food, income and livelihood security services provided by large river–floodplain fisheries.